Analisis Kebutuhan Komik Islami sebagai Suplemen Media Pembelajaran Sistem Sirkulasi untuk SMA/MA: (Analysis of the Requirement for Islamic Comic as a Supplement of The Circulation System Learning Media for SMA/MA) - Andara Vasya Mardiah; Relsas Yogica Relsas Yogica (BIODIK, 2023)
MAN 2 Padang is a school that has different characteristics from the usual public schools. The school which is under the auspices of the Ministry of Religion has an Islamic nuance with its vision, namely "Superior Madrasas and have good morals". This is of course very much in line with the goals of national education in terms of the affective domain contained in the 2013 curriculum in KI-1 and KI-2 which requires the application of social and spiritual attitudes to students. This study aims to determine the need for Islamic comics as a supplement to the circulation system learning media for SMA/MA. The method used is interviews and filling out observation questionnaires by teachers and students. Data analysis used descriptive analysis and the percentage of the results of the number of answers given to all respondents was multiplied by 100%. The results of this study are the unavailability of learning media that includes the application of social and spiritual attitudes that attract students' interest and motivation to learn, especially on the material of the circulation system. So it can be said that the need for the development of Islamic comics as a supplement to the circulation system learning media for SMA/MA. Key words: Develeopment, Islamic Comic, Circulation System Â  ABSTRAK MAN 2 Padang merupakan sekolah yang memiliki karakteristik berbeda dengan sekolah umum biasanya. Sekolah yang berada di bawah naungan Kementerian Agama ini bernuansa islami dengan visinya yaitu â€œMadrasah yang unggul dan berakhlaqul karimahâ€. Hal ini tentu sangat sesuai dengan tujuan pendidikan nasional dari segi ranah afektif yang tertuang dalam kurikulum 2013 pada KI-1 dan KI-2 yang menuntut adanya penerapan sikap sosial dan spiritual pada peserta didik. Penelitian ini bertujuan untuk mengetahui kebutuhan komik Islami sebagai suplemen media pembelajaran sistem sirkulasi untuk SMA/MA. Metode yang digunakan adalah berupa wawancara dan pengisian angket observasi oleh guru dan peserta didik. Data analisis menggunakan analisis dekripstif dan persentase dari hasil jumlah jawaban yang diberikan dibagi jumlah seluruh responden dikali 100%. Hasil penelitian ini adalah belum tersedianya media pembelajaran yang mencakup penerapan sikap sosial dan spiritual yang menarik minat dan motivasi belajar peserta didik khususnya pada materi sistem sirkulasi. Sehingga dapat disimpulkan bahwa perlunya pengembangan komik islami sebagai suplemen media pembelajaran sistem sirkulasi untuk SMA/MA. Kata kunci: Pengembangan, Komik Islami, Sistem Sirkulasi